Insights on First Nations Humanities - Henderson, James (Sákéj) Youngblood (The Australian Journal of Indigenous Education, 2005)
Abstract The question of what is humanity and how it is expressed has endless and dynamic answers. My paper is an attempt to construct and explain the answer based on the insights Indigenous humanity expressed in the continent called North America. The four fundamental insights are organised around the concept of creation as ecology, the insights of embodied spirits, the implicate order, and transformation. These complementary insights inform the depth of Indigenous worldview. These insights are replicated and revealed in structure and meaning of Indigenous languages, ceremonies and stories. These cognitive insights suggest a starting point for reflecting about whatever is most significant in Indigenous humanities in curriculum.